Determination of microbiological quality of packed and unpacked bread - Khanom, Afsana; Shammi, Tahmina; Kabir, Md Shahidul (Stamford Journal of Microbiology, 2017)
Wheat and flour contain essential nutrients such as carbohydrate, minerals, fats and proteins which may aid proliferation of microorganisms in products made from cereal grains and kept under improper storage condition. This study was conducted to determine the microbial load of bread and flour sold in packed and unpacked forms by the local and super markets in Dhaka city. Socioeconomic background, awareness of the microbiological contamination, spoilage of bread and flour and hygiene status of the salespeople were also studied to determine any correlation between the contamination of bread and flour sold by local and super markets. About 20 samples of flour (n=10) and bread (n=10) were included in this study to determine the load of total heterotrophic bacteria (THB), total Staphylococcus aureus (TSA), total Enterobacteriaceae (TE), total coliforms (TC), total yeast and mold (TYM). Equal number of unpacked (local market) and packed (supermarket) bread and flour samples were included in this study. TC, TSA and THB counts were found to be ~1.0 log10 cfu/g higher in unpacked (local market) flour samples compared to those of packed (supermarket) samples. TSA counts were significantly higher in unpacked (local market) samples compared to the packed samples (p<0.05). Food handlers of both the groups did not have adequate knowledge and training on food contamination and spoilage. However, salespeople in the supermarkets were found to be more educated, experienced than those in the local markets. This study demonstrates that unpacked (local market) bread and flour are more contaminated than the packed (supermarket) samples and may pose risk of foodborne infection to consumers. Stamford Journal of Microbiology, Vol.6(1) 2016: 24-29